GAGASAN KRIMINALISASI TERHADAP PELECEHAN SEKSUAL SECARA VERBAL DALAM PEMBAHARUAN HUKUM PIDANA DI INDONESIA - Indah Aidina Prihadi; Emilda Firdaus; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Sexual violence is a violation of human rights, crimes against human dignity, and forms of discrimination. One form of sexual violence is sexual harassment. Sexual harassment is the behavior of approaches related to unwanted sex, including requests for sex, and other behaviors that verbally or physically refer to sex. One of the problems regarding sexual harassment is verbal sexual abuse which is increasingly widespread considering there is no awareness of being able to reduce or ensnare perpetrators into a sentence.This type of research can be classified in normative legal research, namely legal research conducted by examining library materials. In this research, we focus on legal principles. Data collection techniques used in hormonal law research is a library research method that is utilizing the library as a means of collecting data, by studying books as reference material related to the problem to be examined.The conclusions that can be obtained from the results of the study are First, a clear and unequivocal arrangement does not yet exist against verbal sexual harassment in the renewal of criminal law in Indonesia. This is due to verbal or sexual abuse in the Criminal Code (KUHP) or other regulations that still do not regulate verbal sexual abuse or sexual abuse as a criminal act that occurs in the community. so the impact is also still there and law enforcement cannot yet be done. Second, the limitation on the criteria for verbal sexual harassment in criminal law reform in Indonesia still does not provide certainty related to the criteria for verbal sexual harassment. This can be seen in the Criminal Code (KUHP) and other regulations. When seen in the Criminal Code (KUHP), sexual harassment cannot be internalized. The Criminal Code (KUHP) only recognizes the term obscene deeds regulated in Articles 289-296 with the meaning of acts that violate decency, heinous acts and in lustKeywords: Ideas, Criminalization, Acts of Sexual Harassment, Verbals, Criminal Law Reform,